Three new species of Mitracarpus Zucc. (Rubiaceae) from Brazil - Cabral, Elsa Leonor; Sobrado, Sandra V.; Souza, Elnatan Bezerra de (2013)
Three new species of Mitracarpus Zucc. (Rubiaceae). Mitrocarpus carajasensis E. L. Cabral, Sobrado & E. B. Souza, Mitrocarpus federalensis E. L. Cabral, Sobrado & E. B. Souza and Mitrocarpus fernandensii E. L. Cabral, Sobrado & E. B. Souza, from Brazil, are described, illustrated and compared to related taxa.
il., fot. byn
Keywords: Rubiaceae; Mitrocarpus; Taxonomy; Brazil